PENGARUH PENGGUNAAN MEDIA BOOKLET METAMORFOSIS TERHADAP HASIL BELAJAR PADA PEMBELAJARAN IPA SISWA SD KELAS 4 DI SANGGAR BELAJAR PANDAN MALAYSIA - Qolbi, Jihan Fairuz; Syamsuyurnita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is to investigate how learning outcomes are impacted by the usage of booklet media of fourth-grade primary school pupils at Sanggar Belajar Pandan Malaysia on the subject of metamorphosis. This study's backdrop is the low comprehension of metamorphosis content among students, which is said to be brought on by the learning media's lack of attractiveness and diversity. A quantitative experiment is the research method employed, with 16 students serving as the population and sample. The instrument consisted of a pre-test also post-test with give them multiple choice questions. Students' average pre-test score was 50.9, according to the analysis's findings, while their post-test score rose to 75.18. The findings of the hypothesis test showed a p-value of 0.000 with a paired sample test, which implies that the use of booklet media has a substantial impact on student learning outcomes. This study presents guidelines for the use of cutting-edge learning materials in the scientific teaching process at the elementarry school level in addition to determining that booklet media effectively boost students’ grasp of methamorphosis subject. It is expecteed that the findings of this study will contribute to develop the learning materials that are more relevant and engaging while also meeting students’ needs.